Nutrient utilization and carcass traits in broiler chickens as affected by nano-chromium supplementation - KUMARI, RENU; KUMAR, ASHOKA; PALOD, JYOTI; MONDAL, B C; SINGH, SANJAY (The Indian Journal of Animal Sciences, 2023)
The present study was carried out to perceive the effects of dietary supplementation of nano-chromium on nutrient utilization and carcass traits in broiler chickens. For this, 120 unsexed day-old broiler chickens were procured and randomly allocated into four different treatment groups with three replicates in each. The control group (T0) was fed with a standard basal diet as per BIS (2007). Treatment groups T1, T2, and T3 were fed the basal diet with 400, 800, and 1600 ppb levels of nano-chromium, respectively for six weeks. Dry matter, crude protein, and total carbohydrate metabolizability were significantly improved in treatment groups T2 and T3; while organic matter and ether extract retention were found significantly higher in treatment groups T1, T2, and T3 when compared with a control group. There was no significant difference in the yield of cut-up parts (% live body weight). The supplementation of nano-chromium did not bring any significant changes in processing loss i.e. blood, feather, head, and shank, but abdominal fat was significantly reduced with increasing levels of nano-chromium. Hence, it can be concluded that dietary supplementation of 1600 ppb nano-chromium in the diet of broiler chicken improved nutrient utilization and lowered abdominal fat in broiler chicken.